Electrical Performance Test Design for Speed Sensor Torque Flow, Rear Brake, and Solenoid ECMV Power Train HD785-7 at PT XYZ - Setia Abikusna; Diki Ramadhani; Leo Setiawan; Lukyawan Pama Deprian; Randy Putra Afani (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
PT XYZ's Component Exchange (COMEX) Department has 8 Quality Assurance Processes, one of which is performance test (QA6). The performance test is conducted to evaluate the condition of overhauled components. From January to February 2024, the COMEX Department experienced issues with electrical components in the Power Train area, specifically the Electronic Control Modulating Valve (ECMV) solenoid, torque flow speed sensor, and rear brake speed sensor. Currently, the functional inspection tool for the solenoid only uses an Arduino as a power supply and an impact wrench as a substitute for the gear shaft to inspect the torque flow speed sensor and rear brake speed sensor. The results from these inspections are inaccurate, leading to rework on the transmission components and the brake final drive of the HD785-7. The 8-step method was used to address these issues. This method includes Determining Themes, Current Condition Analysis, Target Setting, Root Cause Analysis, Improvement Plan, Improvement Implementation, Result Evaluation, Standardization and Improvement Plan. Improvements included creating an electrical performance test tool, developing work instructions for using the tool, and establishing a reusable parts standard. The tool successfully reduced the rework of electrical parts, achieving a 100% reduction in rework from January-February 2024 to April-June 2024.